2006
DOI: 10.1002/bjs.5302
|View full text |Cite
|
Sign up to set email alerts
|

The examination assessment of technical competence in vascular surgery

Abstract: Current surgical examinations do not address technical competence. This model appears to be a valid assessment of technical skills in an examination setting. The standards are set at a level appropriate for a specialist vascular surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 31 publications
0
38
1
1
Order By: Relevance
“…Compared against other measures of technical proficiency in the simulation setting (such as hand motion analysis (Pandey et al 2004(Pandey et al , 2006Datta et al 2006;Leong et al 2008), efficiency ratings (Datta et al 2004), time (Goff et al 2001;VanHeest et al 2012) or product scores (Datta et al 2004)), the OSATS scores have generally shown positive relationships. Conversely, for measures that are less about technical proficiency, such as oral examinations (Pandey et al 2006) or assessments that focus on communication skills (LeBlanc et al 2009;Black et al 2010;Ponton-Carss et al 2011) or professionalism (Ponton-Carss et al 2011, the correlations are lower and less consistently positive. This evidence supports the validity argument for the OSATS, in that we would predict low correlations between unrelated constructs (such as technical skills and communication skills).…”
Section: Relationships With Other Measuresmentioning
confidence: 96%
See 1 more Smart Citation
“…Compared against other measures of technical proficiency in the simulation setting (such as hand motion analysis (Pandey et al 2004(Pandey et al , 2006Datta et al 2006;Leong et al 2008), efficiency ratings (Datta et al 2004), time (Goff et al 2001;VanHeest et al 2012) or product scores (Datta et al 2004)), the OSATS scores have generally shown positive relationships. Conversely, for measures that are less about technical proficiency, such as oral examinations (Pandey et al 2006) or assessments that focus on communication skills (LeBlanc et al 2009;Black et al 2010;Ponton-Carss et al 2011) or professionalism (Ponton-Carss et al 2011, the correlations are lower and less consistently positive. This evidence supports the validity argument for the OSATS, in that we would predict low correlations between unrelated constructs (such as technical skills and communication skills).…”
Section: Relationships With Other Measuresmentioning
confidence: 96%
“…This evidence supports the validity argument for the OSATS, in that we would predict low correlations between unrelated constructs (such as technical skills and communication skills). Of note, OSATS performance did not correlate with operative logbook scores that were a measure of the number of live procedures performed and the amount of supervision per procedure (Pandey et al 2006).…”
Section: Relationships With Other Measuresmentioning
confidence: 99%
“…In addition to its educational value, there is interest in using simulation for the objective assessment of technical skill, including as part of summary assessment at the completion of training [13]. Presumably, these tools are used to assess readiness for the OR, where time constraints and safety concerns have altered the educational environment.…”
mentioning
confidence: 98%
“…An OSATS has been used and validated in relation to the European Board Examination in Vascular Surgery. 5 In Denmark, vascular surgery is a relatively small specialty with 7 dedicated pure vascular departments, and the specialized training for vascular surgery lasts 6 years. The first year of this period is an introduction to vascular surgery, and it is based on specific goals that give both the trainee and the vascular surgical unit the possibility to evaluate whether the choice of specialty is the right one.…”
Section: Introductionmentioning
confidence: 99%